2023
DOI: 10.3389/fneur.2023.1170215
|View full text |Cite
|
Sign up to set email alerts
|

Stress hyperglycemia as a modifiable predictor of futile recanalization in patients undergoing mechanical thrombectomy for acute ischemic stroke

Abstract: IntroductionMechanical thrombectomy (MT) is the first line treatment in acute ischemic stroke (AIS) due to large vessel occlusion (LVO). Approximately half of patients treated with MT does not have a favorable outcome 3 months after stroke. The aim of this study was to identify predictors of futile recanalization (FR) in patients with LVO treated with MT.MethodsA retrospective analysis of consecutive patients with acute ischemic stroke due to anterior circulation LVO who underwent MT. Patients with a TICI scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…The association between stress hyperglycemia and futile recanalization has already been reported by Merlino et al [25]. Since GAR is a strong predictor of poor prognosis, they suggest that, in future studies, the management of stress hyperglycemia should not be based on absolute glucose levels but on GAR levels.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The association between stress hyperglycemia and futile recanalization has already been reported by Merlino et al [25]. Since GAR is a strong predictor of poor prognosis, they suggest that, in future studies, the management of stress hyperglycemia should not be based on absolute glucose levels but on GAR levels.…”
Section: Discussionmentioning
confidence: 60%
“…Since GAR is a strong predictor of poor prognosis, they suggest that, in future studies, the management of stress hyperglycemia should not be based on absolute glucose levels but on GAR levels. Furthermore, they suggest paying special attention to patients who have undergone MT for anterior circulation LVO with a GAR index of 17.9 or higher [ 25 ]. However, in our study, there were no statistically significant differences in stress hyperglycemia, HbA1c, or the GAR index.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia in AIS patients treated with MT aggravates oxidative stress and endothelial cell damage, causing reperfusion injury to brain tissue, thus leading to a poor patient prognosis [ 37 , 38 ]. Giovanni Merlino et al reported that stress hyperglycemia is a modifiable predictor of futile recanalization in patients with large vessel occlusion treated with MT [ 39 ]. Hyperglycemia may promote futile recanalization by through lactate production and intracellular acidosis, disrupting the blood–brain barrier and affecting cerebrovascular autoregulation to cause reperfusion injury and hemorrhagic transformation [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the association between TGI levels and the outcomes of patients undergoing thrombolysis ( 24 , 53 ), while there were no studies on the effect of TGI on the outcomes in patients who underwent MT. According to Merlino’s study, stress hyperglycemia is strictly and independently associated with futile recanalization in patients undergoing MT ( 61 ). Thus, further study focus on the predictive value of TGI on the outcome of patients treated with MT is promising.…”
Section: Discussionmentioning
confidence: 99%